Trust in Government in Times of Crisis: A Quasi-Experiment During the Two World Wars - Ahmed Skali; David Stadelmann; Benno Torgle (Center for Research in Economics, Management and the Arts (CREMA), 2019)
Do crises erode trust in government? To answer this question, we leverage the quasi-experimental setting of the sharply increased military threat to the neutral county of Switzerland during the two world wars as an exogenous shock. In doing so, we exploit a unique feature of Swiss politics: government issuance of pre-referenda voting recommendations. We use constitu ent adherence to government recommendations as a behaviour al proxy for trus t in government, measured in real time prior to, duri ng, and after the crisis. Our difference-in- differences estimates provide strong evidence that constituents are significantly less likely to follow governmental voting recommendations during wartime.
Keywords: D72; D74; H56; H79; 330; Trust in Government; Crisis; WWII; World War II; Referenda; Switzerland